Cellulase immobilization on TEOS encapsulated and APTES functionalized magnetic nanoparticles (MNPs) - Rashid, Shah Samiur; Sikder, Md. Belal Hossain; Mohd Hasbi, Ab Rahim; Aizi Nor Mazila, Ramli; Rasidi, Roslan (IOP Publishing, 2021)
Immobilized enzymes are more stable and more resistant to environmental changes in contrast to free enzymes in solution. Magnetic nanoparticles (MNPs) are potential immobilization supports materials for enzymes and easily recovered for reuse. It has low toxicity effects and fast separation from reaction mixtures simply by use of external magnets. Enzyme immobilization technology also helps to boost the enzyme’s properties by using the technique to keep it in separate support or matrix. The aim of immobilization is to render the enzyme immobile so that it is reusable during the reaction, which leads to a more efficient process and easy separation from the substance. The aims of this investigation were to encapsulate (coat) and functionalize MNPs by using TEOS and APTES respectively for reusable cellulase immobilization on that as a supports matrix. The silicon encapsulation with TEOS and amino functionalization of synthesized MNPs was confirmed by the FT-IR and XRD. Cellulase was immobilized successfully on that nanoparticles and also confirmed by FT-IR, cellulase assay. The immobilized enzymes showed a satisfactory level of reusability (51%) after 10 consecutive reaction cycles.